Pathological left ventricular hypertrophy and outflow tract obstruction in an infant of a diabetic mother: A case report - AS, Ujuanbi; CA, Onyeka; WS, Yeibake; T, Oremodu; OE, Kunle-Olowu; BE, Otaigbe (Journal of Cardiology and Cardiovascular Medicine, 2020)
Background: Infants of diabetic mothers (IDMs) are at increased risk of developing congenital anomalies including cardiac defects. Pathological left ventricular hypertrophy, asymmetrical septal hypertrophy and outflow tract obstruction is a rare but known cardiac comorbidity in infants of diabetic mothers. The severity of this condition in IDMs can vary from an incidental finding on echocardiography to an infant with severe symptoms of congestive heart failure and specific management of the condition varies. Aim: The aim of this article is to report this clinical entity in a Nigerian infant born to a mother with poor glycaemic control in pregnancy and highlight management. Case report: We report a term neonate who was diagnosed as a case of pathological left ventricular hypertrophy, asymmetrical septal hypertrophy and outflow tract obstruction delivered to a mother with gestational diabetics with poor glycaemic control in pregnancy. Child was treated successfully with β-adrenergic blocker and showed resolution of hypertrophy in follow-up echocardiography. Conclusion: Infants of diabetic mothers are very high risk infants. Pathological left ventricular hypertrophy in IDM have good prognosis. Early recognition and prompt intervention is advocated.